Usage of Technology in Promoting Well-being of Senior Citizens - Dr. Radhika Kapur, (Indian Journal of Data Mining (IJDM), 2024)
In the present existence, with advancements taking place and with the advent of modernization, the utilization of technologies have acquired prominence. The internet is regarded as one of the eminent factors that is utilized in augmenting information in terms of all subjects and concepts. Furthermore, individuals are able to obtain answers to all types of questions that are overwhelming to them. The senior citizens make use of technologies and internet for number of purposes. In addition, they are required to obtain help from others as well in putting into operation different tasks and activities in a well-ordered manner. In cases of visual impairments and other types of health problems and illnesses, the senior citizens are unable to carry out job duties on their own, hence, they are required to obtain help from others. The senior citizens are not only incurring the feeling of satisfaction, but they are able to contribute efficiently in leading to up-gradation of overall standards of living, when they are making use of different types of technologies and internet. The senior citizens in some cases are overwhelmed by feelings by apprehensiveness and vulnerability. But understanding the concepts and getting engaged in regular practice will be facilitating in honing technical skills. Therefore, the role of technology is considered important in promoting well-being of senior citizens. The main concepts that are taken into account in this research paper are, understanding the meaning and significance of technologies, factors highlighting usage of technology in promoting well-being of senior citizens and measures to be implemented in augmenting technical skills by senior citizens.